The Relationship between Chronic Energy Deficiency and The Incidence of Anemia in Pregnant Women at The Maiwa Community Health Center, Enrekang Regency - Fitriani; Nurdin , Nasrayanti; Laela, Nur; Fatmawati (Jurnal Midwifery, 2026)
Pregnant women who experience the risk of chronic energy deficiency (CED) will cause several problems, both for the mother and the fetus. KEK in pregnant women can cause risks and complications in the mother, including anemia, bleeding, the mother's weight does not increase normally, and being exposed to infectious diseases This study aims to determine the relationship between chronic energy deficiency and the incidence of anemia in pregnant women at the Maiwa Health Center UPT, Enrekang Regency This study was conducted from 01 to 30 June 2025. The population in this study were all pregnant women at the Maiwa Health Center UPT, Enrekang Regency. The sample in this study was some of the pregnant women at the Maiwa Health Center UPT, Enrekang Regency, as many as 30 people with purposive sampling The results of the study showed that out of 30 people who were used as samples, 7 pregnant women had KEK (23.3%) and 23 people did not experience KEK (76.7%). The results of the study showed that out of 30 people who were used as samples, 12 pregnant women had anemia (40.0%) and 18 people did not experience anemia (60.0%). The results of the study showed a relationship between KEK in pregnant women and the incidence of anemia, obtained a value of ρ = 0.009 <from α = 0.05 It is recommended to improve the quality of health services for pregnant women, including early detection and treatment of anemia and KEK with joint efforts between pregnant women, families, health workers, and the community, it is hoped that the problem of anemia and KEK in pregnant women can be overcome, so that they can give birth to a healthy and quality generation.